Morphological characterization of bottle gourd [Lagenaria siceraria (Mol.) Standl.] - Virendra Kumar,; Anil Kumar,; Akhil Kumar Chaudhary,; Suman Poonia,; Shyam Prakash,; Nimit Singh,; Pravesh Kumar,; Hradesh Shivahare, (The Bioscan, 2025)
The morphological characterization of bottle gourd [Lagenaria siceraria (Mol.) Standl.] was undertaken to evaluate genetic diversity and generate valuable information for breeding programmes. A total of forty-six genotypes including nine promising parental lines and 36 hybrids were assessed at Acharya Narendra Deva University of Agriculture and Technology, Ayodhya, Uttar Pradesh, during the Zaid seasons of 2023-24 and 2024-25. Morphometric observations were recorded on 18 traits, including vine length, stem internodes, leaf shape, tendril branching, fruit characteristics and seed shape. Significant genetic variation was observed across genotypes, particularly in fruit traits such as shape, skin colour and blossom-end structure. The findings underscore the importance of genetic diversity in bottle gourd for developing improved varieties with desirable agronomic traits. This study establishes a foundation for crop improvement.